Avaliação eletroneuromiográfica em pacientes com artrite reumatóide - Vasconcelos, José Tupinambá Sousa (2001)
INTRODUCTION: Rheumatoid Arthritis (RA) is a chronic systemic inflammatory disease mainly characterized by symmetric joint damage. Extraarticular involvement can be eventually present, but are usually subclinical. Neuromuscular disorders have been reported and can complicate RA at any time during its course. However, it is often difficult to diagnose early or slight neuropathies and muscular problems in a set of patients with joint pain and limitations of movement caused by RA itself. OBJECTIVES: The main goal of our study was to describe the peripheral neuromuscular system abnormalities in adult RA patients using electroneuromyography (ENM), thus determining their prevalence. Potential correlation between electrophysiological fíndings and demographic, clinicai, laboratorial and radiographic data were also examined. PATIENTS AND METHODS: Sixty four adult RA patients were enrolled for this study. Clinicai evaluation included: duration of disease and moming stiffness, tender and swollen joint count, physician and patient global assessment of disease activity, quantitative assessment of pain by visual analog scale, functional status assessment and Health Assessment Questionnaire (HAQ). Erythrocyte sedimentation rate and serum rheumatoid factor were also measured. All patients had hands X-ray examination and Sharp’s method was used to evaluate joint damage. ENM was performed in all patients. RESULTS: Electrophysiologic abnormalities were found in 14 (21.9%). RA patients. Carpal tunnel syndrome (CTS), the most prevalent abnormality, was detected in 9 patients (14.1%) and peripheral polyneuropathy (PPN) was present in 8 patients (12.5%). PPN associated to CTS was observed in 3 patients (4.7%) and one atient (1.6%) presented PPN associated with ulnar nerve compression at the elbow. n half of the PPN cases, only sensitive neural fibers were involved. In the other half, notor involvement was also detected. The primary pattem lesion was axonal loss in ill cases with PPN. Compressive neuropathy was present in 50% of patients with 3PN. There was statistically significant correlation between the presence of ENM ibnormalities and duration of disease (p < 0,001). On the other hand, electrophysiologic abnormalities were not correlated to any other demographic, clinicai, laboratorial or radiographic parameter evaluated. CONCLUSION: Neuromuscular disorders are frequent extraarticular manifestation of RA. Carpal tunnel syndrome and peripheral polyneuropathy are the most prevalent disorders and the association- of compressive and non-compressive peripheral neuropathies may occur. Electroneuromyography provide an easy and non-invasive method of evaluating objectively the existence, type and distribution of neuromuscular problems in RA.